2020
DOI: 10.1055/a-1224-6115
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Medicinal Plants of Veterinary Importance: A Literature Review

Abstract: Viruses have a high mutation rate, and, thus, there is a continual emergence of new antiviral-resistant strains. Therefore, it becomes imperative to explore and develop new antiviral compounds continually. The search for pharmacological substances of plant origin that are effective against animal viruses, which have a high mortality rate or cause large economic losses, has garnered interest in the last few decades. This systematic review compiles 130 plant species that exhibit antiviral activity on 37 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 95 publications
0
10
0
1
Order By: Relevance
“…So far, many rhabdovirus strains have been isolated and identified from wild or farmed fish bodies around the world in recent decades [ 17 ]. Revealing the infection and pathogenic mechanisms of fish rhabdoviruses is vital for the construction of antiviral techniques and development of vaccine or antiviral drugs in the future [ 18 ], as one strain of fish rhabdovirus, SCRV, could infect some kinds of fish and activate the typical programmed apoptotic cell death [ 19 ]. Recent research confirmed that it could activate autophagy via the PI3K/Akt-mTOR pathway in one fish cell line, Chinese perch brain (CPB) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, many rhabdovirus strains have been isolated and identified from wild or farmed fish bodies around the world in recent decades [ 17 ]. Revealing the infection and pathogenic mechanisms of fish rhabdoviruses is vital for the construction of antiviral techniques and development of vaccine or antiviral drugs in the future [ 18 ], as one strain of fish rhabdovirus, SCRV, could infect some kinds of fish and activate the typical programmed apoptotic cell death [ 19 ]. Recent research confirmed that it could activate autophagy via the PI3K/Akt-mTOR pathway in one fish cell line, Chinese perch brain (CPB) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some constituents with relevant pharmacological activity have been identified. For example, in vitro studies demonstrated the antiviral activity of various constituents of medicinal plants, e.g., quercetin, carvacrol, or theaflavins [ 111 ], as well as antibacterial activity of flavonoids [ 112 ], isothiocyanides [ 113 ], hydroquinone, and umbelliferone [ 114 ].…”
Section: Biologically Active Compounds Of Herbal Preparationsmentioning
confidence: 99%
“…Antivirals might be useful in controlling and managing PRRSV, and recent studies have reported the ability of herbal extracts to inhibit PRRSV infection [ 6 8 ]. Many compounds derived from natural sources such as plants have shown inhibitory activity against viruses and a wide variety of pathogens [ 9 , 10 ]. Several natural compounds have demonstrated antiviral activity (for instance, immense potential for inhibiting viral replication) and drug-like activity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds derived from natural sources such as plants have shown inhibitory activity against viruses and a wide variety of pathogens [ 9 , 10 ]. Several natural compounds have demonstrated antiviral activity (for instance, immense potential for inhibiting viral replication) and drug-like activity [ 10 ]. The identification of potent inhibitors of PRRSV from natural sources is challenging, as it requires compound extraction and evaluation of antiviral activity, both of which require funds and specific experimental equipment.…”
Section: Introductionmentioning
confidence: 99%